2014
DOI: 10.1111/jocd.12113
|View full text |Cite
|
Sign up to set email alerts
|

Nail changes and disorders in elderly Egyptians

Abstract: The prevalence of nail changes and disorders has increased among elderly patients although they are frequently overlooked by health care providers. Dermatologist should be aware about various nail changes related to aging and those associated with other dermatoses or systemic diseases. Histopathologic picture can enhance the accuracy of clinical diagnosis of various nail changes and disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…32 A recent study on nail changes in 400 elderly Egyptians, half aged greater than 60, found onychorrhexis in 45.5% of subjects. 33 Another study looking at 68 participants with brittle nails and 70 without noted that 20.59% of those with brittle nails had onychorrhexis, and onychorrhexis was only found in 1.43% of those with non-brittle nails. 34 Although the prevalence of rough onychorrhexis, and even onychorrhexis, is not known, it is thought that brittle nails themselves are prevalent in approximately 20% of the population, with females being twice as likely to experience this nail change.…”
Section: Discussionmentioning
confidence: 99%
“…32 A recent study on nail changes in 400 elderly Egyptians, half aged greater than 60, found onychorrhexis in 45.5% of subjects. 33 Another study looking at 68 participants with brittle nails and 70 without noted that 20.59% of those with brittle nails had onychorrhexis, and onychorrhexis was only found in 1.43% of those with non-brittle nails. 34 Although the prevalence of rough onychorrhexis, and even onychorrhexis, is not known, it is thought that brittle nails themselves are prevalent in approximately 20% of the population, with females being twice as likely to experience this nail change.…”
Section: Discussionmentioning
confidence: 99%